Search for supersymmetry using final states with muons, jets, and missing transverse momentum with the CMS detector in √ s = 7 TeV pp collisions - Lukyanenko, S.T.; Obikhod, T.V. (Вопросы атомной науки и техники, 2015)
The results of search for superparticles in final states with jets, muons and missing transverse energy are presented. The study is based on a data obtained in proton-proton collisions at √s = 7 TeV. They correspond to 4.36 fb⁻¹ of integrated luminosity collected with the CMS detector in 2011. mSUGRA/MSSM model built in generator PYTHIA6 was used for SUSY signal modeling. Two selection criteria for searching SUSY- manifesting were used. Background from Standard Model processes was estimated using the MADGRAPH and POWHEG generators. It is shown that with confidence level 95% the data are found to be in agreement with Standard Model expectations and new physics effects are not observed in ranges ETmiss >200 GeV and Meffinc >600 GeV. Наведено результати пошуку суперчастинок із мюонами, струменями і втраченою поперечною енергією в кінцевому стані. Вивчення ґрунтується на даних, отриманих при протон-протонних зіткненнях при енергії √s = 7 ТеВ, що відповідають інтегрованій світимості 4.36 fb⁻¹, накопиченій CMS детектором в 2011 році. Для моделювання SUSY сигналу використовувалась модель mSUGRA/MSSM, вбудована в пакет PYTHIA6. Розглядалось два критерії відбору для пошуку SUSY подій. За допомогою генераторів MADGRAPH и POWHEG були оцінені фони, обумовлені процессами Стандартної Моделі. Показано, що з рівнем довіри 95% отримані результати знаходяться у відповідності із передбаченнями Стандартної Моделі і в межах ETmiss >200 ГеВ і Meffinc >600 ГеВ ефекти нової фізики не спостерігаються. Представлены результаты поиска суперчастиц с мюонами, струями и потерянной поперечной энергией в конечном состоянии. Изучение основано на данных, полученных в протон-протонных столкновениях при энергии √=7 ТэВ и соответствующих интегральной светимости 4.36 fb⁻¹ , накопленной CMS детектором в 2011 году. Для моделирования SUSY сигнала использовалась модель mSUGRA/MSSM, встроенная в пакет PYTHIA6. Рассматривалось два критерия отбора для поиска SUSY событий. С помощью генераторов MADGRAPH и POWHEG были оценены фоны, обусловленные процессами Стандартной Модели. Показано, что с уровнем доверия 95% полученные результаты находятся в согласии с предсказаниями Стандартной Модели и в пределах ETmiss >200 ГэВ и Meffinc >600 ГэВ эффекты новой физики не наблюдаются.